Unraveling the therapeutic potential of Elaeagnus angustifolia extract on triple-negative breast cancer (TNBC): An investigation using zebrafish model - Haya Abuhijleh; Zain Zakria; Hiba Bawadi; Ayat Hammad; Ala-Eddin Al Moustafa; Abdullah Shaito; Maha Al-Asmakh (PLoS ONE, 2026)
Breast cancer is a widespread and aggressive disease, with 2.3 million new cases globally in 2022. Metastasis, the spread of cancer cells to distant organs, remains a leading cause of breast cancer-related mortality. Current treatment options, particularly traditional chemotherapeutic drugs, are often associated with severe side effects, emphasizing the urgent need for safer and more effective therapeutic alternatives. Triple-negative breast cancer (TNBC) represents one of the most aggressive breast cancer subtypes, characterized by the absence of estrogen receptors (ER), receptors (PR), and HER2 expression. The human TNBC cell line MDA-MB-231, was selected in this study due to its aggressive, metastatic phenotype and its well-established use in zebrafish xenograft models. This makes it a highly relevant platform for preliminary in vivo evaluation of novel plant-derived compounds, particularly those targeting hard-to-treat breast cancer subtypes such as TNBC. Elaeagnus angustifolia (EA), commonly known as Russian olive, has attracted interest for its antimicrobial, anti-inflammatory, and antioxidant properties. However, its potential anticancer activity, especially against TNBC, remains relatively unexplored. This research investigated the efficacy of EA extract against MDA-MB-231 TNBC cells using a wild-type AB zebrafish model. A key objective was to evaluate the toxicological profile of EA across multiple physiological parameters in zebrafish, including developmental, cardiovascular, neuromuscular, and hepatic functions. The study identified safe, non-toxic concentrations of EA extract (0.5 mg/mL and 0.75 mg/mL). Moreover, treatment with EA in zebrafish xenografts led to a dose-dependent reduction in fluorescence intensity of injected TNBC cells, suggesting suppression of tumor cell proliferation and survival.. These findings suggest that EA warrant further investigation as a potential anticancer agent for TNBC. The observed safety profile and preliminary anti-tumor effects in zebrafish provide a foundation for future mechanistic and mammalian studies.